Effective SERS method for identification of dexmedetomidine hydrochloride in biological samples. Issue 12 (12th March 2020) - Han, Siqingaowa; Zhang, Chen; Sha, Xuanyu; Li, Nan; Hasi, Wuliji; Zhang, Yanhua
Abstract : An effective SERS method was employed to identify dexmedetomidine hydrochloride in two biological samples: urine and serum. Abstract : In recent years, the abuse of dexmedetomidine hydrochloride (DH) in various criminal cases has increased demand for the rapid and effective supervision and determination of DH. In this paper, based on the SERS method, DH in aqueous solution, urine and serum was effectively and sensitively detected. On the basis of density functional theory (DFT), the Raman peaks of DH were identified by systematic calculation. The SERS performance for the measurement of DH was compared between Ag colloid and paper-based substrate. It was found that Ag colloid together with KI as an aggregator was equipped with better SERS behavior and could thus be applied in the analysis of DH in biological samples. Furthermore, with simple pre-treatment, DH in urine and serum were successfully determined with detection limits down to 10 μg mL −1 and 12 μg mL −1, respectively. The linear relationships between the characteristic peak intensity and the concentration of DH in urine and serum were established and the recovery rates were calculated with low relative standard deviation (RSD). This fast, accurate and non-destructive SERS method lays a reliable foundation for rapid on-site detection of DH.